Nutrient foraging ability promotes intraspecific competitiveness in the clonal plant Hydrocotyle vulgaris. (May 2022) - Zhang, Li-Min; Alpert, Peter; Yu, Fei-Hai
Highlights: Spatial heterogeneity in soil nutrients is ubiquitous in natural habitats. Nutrient foraging ability differs between clones within species. Intraspecific competition of clonal plants are comprised of within- and between-clone competition. Foraging and between-clone competitiveness were positively related when nutrients were patchy. Foraging and within-clone competitiveness were negatively related when nutrients were patchy. Abstract: Many plant species forage for nutrients by accumulating more biomass or ramets where soil nutrient availability is high. Nutrient foraging ability differs between species and between genotypes within species, can increase plant performance when nutrients are patchy, and may lead to differences in competitive ability and have community-level effects. Effects of intraspecific variation in nutrient foraging ability could be particularly strong in clonal species, in which individual genotypes can form large clones and persist for long times. We tested the hypotheses that clones with greater foraging ability (1) have greater ability to compete with other clones of the same species but (2) experience greater competition within a clone. Sets of clonal fragments of five clones of the perennial, creeping herb Hydrocotyle vulgaris were grown alone, with a fragment of a different clone, or with a second fragment of the same clone in pots with a uniform or patchy distribution of soil nutrients. Consistent with the first hypothesis, foraging ability and between-clone competitiveness as measured by less negative competitive response were positively related when nutrients were patchy but not when they were uniform. Contrary to the second hypothesis, foraging and within-clone competitiveness were negatively related. Intraspecific competition both between and within clones could thus select for greater foraging ability. If this in turn increases ability to compete with other species, it may help explain the dominance of some clonal species.